Spatio-Temporal pattern of coastal flooding due to microclimate change and mangrove deforestation in Semarang and Demak Coastal Area - Widjonarko; Purnaweni Hartuti; Maryono (E3S Web of Conferences)
The coastal area of Semarang-Demak has a high intensity of economic activity, indicated by the presence of industry, housing, and other socio-economic activities. On the one hand, the coastal area of Semarang-Demak is faced with increasing pressure due to climate change, and environmental degradation (mangrove deforestation). The climate change and mangrove deforestation have made the coastal flooding wider. This study is aimed to reveal the relationship between climate change, environmental degradation, and its impact to coastal flooding in Semarang Demak. This study used remote sensing methods uisng Landsat data from the years 1988-2023. The results showed the strong relationship between climate change, mangrove deforestation, and coastal flooding. And they have a significant impact on increasing the area of flooding on the Semarang-Demak coast. The modeling using regression statistics resulted the regression equation Y = -8966.7 + 290.8X1 + 5.06X2, where Y is the area of flooding on the Semarang Demak coast, X1 is mangrove forest damage, and X2 is microclimate change, with a determination coefficient of 74%. Based on this model, the opportunity for an increase in the area of flooding will be even greater if no efforts are made to overcome mangrove damage, and also microclimate change.